2016
DOI: 10.1227/neu.0000000000001042
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Poor Quality of Life 1 Year After Subarachnoid Hemorrhage

Abstract: Reduced QOL affects as many as one-third of SAH survivors 1 year after SAH. Delayed infarction is the most important in-hospital modifiable factor that affects QOL. Increased attention to cognitive and emotional difficulties after hospital discharge may help patients achieve greater QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 41 publications
4
84
1
5
Order By: Relevance
“…The mean time in our ICU was 19 days (4-76 days; SD +/− 9.8) with a median stay of 17 days. This is a relatively high LOS compared to other studies 3,7,8,19,26 . For example, Dasenbrock et al used the data from 7,516 admissions after subarachnoid haemorrhage from the Nationwide Inpatient Sample and reported a median total hospital stay for the population of 16 days (11-23 days) 19 .…”
Section: Discussioncontrasting
confidence: 50%
“…The mean time in our ICU was 19 days (4-76 days; SD +/− 9.8) with a median stay of 17 days. This is a relatively high LOS compared to other studies 3,7,8,19,26 . For example, Dasenbrock et al used the data from 7,516 admissions after subarachnoid haemorrhage from the Nationwide Inpatient Sample and reported a median total hospital stay for the population of 16 days (11-23 days) 19 .…”
Section: Discussioncontrasting
confidence: 50%
“…Fifty-one of 55 studies (93%) used one of the following screening or rating scales to ascertain the presence of depression: Hospital Anxiety Depression Scale (HADS), 18,19,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Beck Depression Inventory (BDI), [12][13][14][15][16][17][18][19][20][21][40][41][42][43][44][45][46][47][48][49][50][51] Center for Epidemiologic Studies Depression (CESD), [22][23][24]52,53 Montgomery Åsberg Depression Rating Scale (MADRS), 54,55 Geriatric Depression Scale (GDS), 56,57 International Classification of Diseases...…”
Section: Resultsmentioning
confidence: 99%
“…RTW is an important factor to consider after a SAH. Previous research has shown that persons with SAH were least satisfied with their vocational situation at follow-up (12) and no-RTW is associated with a poor quality of life (11,21).…”
Section: Discussionmentioning
confidence: 98%